ULTRASTRUCTURE OF THE SCALE OF HILLSTREAM FISH, SCHISTURA MONTANUS (MCCLELLAND) AND ITS PHYLOGENIC SIGNIFICANCE - R. K. NEGI; M. S. JOHAL; Y. K. RAWAL (The Bioscan, 2010)
Adult specimens of Schistura montanus (McClelland) (syn. Nemacheilus kangrae Menon) were collected from Kamal river (78º05’ 36.4" E: 30º58’ 19.8" N; altitude 1375 MSL) of Uttarkashi district of Uttarakhand state, India. In the scale of S. montanus (McClelland), the focus region is neither similar to Indian major carps nor to minnows. The shape and structure of circuli of the scale of S. montanus (McClelland) is similar to the circuli of the scale of Cobitis linea (Heckel) to some extent. It is opined that the generalized structure of the scale of S. montanus (McClelland) is more closer to the cobitid scale of Cobitis linea (Heckel), hence, this scale should also be referred as Cobitid scale because the circuli of the scales of both the fishes show great similarity.